The Effectiveness of Plant Toxins from Butterfly Pea (Clitoria ternatea L., 1753) and Purple Lavender (Lavandula officinalis L., 1753) on Rice Bettle Sitophilus oryzae L. (1758) - Hafida Ilma, Adella Putri; Falahudin, Irham (Berkala Ilmiah Biologi, 2024)
Rice beetle Sitophilus oryzae is one of the pests that must be eradicated because it plays a role in reducing rice quality, especially in storage warehouses.Usually the warehouse staff eradicate the rice beetle Sitophilus oryzae with artificial insecticides. However, artificial insecticides are not very friendly to the environment. Researchers try to bring solutions to these problems. This research describes a solution to create natural insecticides derived from plants. It has been proven that natural insecticides are much more environmentally friendly than artificial insecticides. This research used the simplicia powder of the Butterfly Pea Clitoria ternatea and the Purple Lavender Lavandula afficinalis as a test material to see its toxin ability against the rice beetle Sitophyllus oryzae to cause mortality. Researchers used quantities of 2 grams, 4 grams, 6 grams, and 8 grams which were supplemented with controls on each plant. The results of the data obtained are displayed in graphical form and using a Completely Randomized Design (CRD) and using a further test of Honest Significant Difference (BNJ) using the SPSS ver.25 application to find out the significant difference between the test materials. It can be concluded that the Purple Lavender simplicia powder Lavandula afficinalis can kill the Rice Beetle Sitophyllus oryzae more, with the number of deaths reaching 63 tails and a quantity of 8 grams with the highest mortality rate.